Sewage impact on the composition and distribution of Polychaeta associated to intertidal mussel beds of the Mar del Plata rocky shore, Argentina - Elías Rodolfo (Iheringia: Série Zoologia, 2003)
The polychaete composition and distribution within mussel beds were studied in order to assess organic pollution due to domestic sewage in a rocky shore of Mar del Plata (Argentina) during 1997. Four stations and a control site were randomly sampled around the local effluent. Quantitative data on polychaetes, as well as sediment accumulated among mussels and its organic carbon content were measured. Polychaete distribution patterns are related to the organic matter gradient, being Capitella cf. capitata, Neanthes succinea (Frey & Leuckart, 1847) and Boccardia polybranchia (Haswell, 1885) the dominant indicator species close to the effluent. At medial distances, the cirratulids Caulleriella alata (Southern, 1914) and Cirratulus cirratus (Müller, 1776) are very important in abundance. The syllids Syllis prolixa Ehlers, 1901 and S. gracilis Grube, 1840 are distributed along the study area, but dominate at the medial stations and at the control site. The orbiniid Protoariciella uncinata Hartmann-Schröder, 1962 is subdominant at the control station.